2016
DOI: 10.3390/ijerph13121236
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cotinine Cutoff Values for Smoking Status Classification

Abstract: While cotinine is commonly used as a biomarker to validate self-reported smoking status, the selection of an optimal cotinine cutoff value for distinguishing true smokers from true nonsmokers shows a lack of standardization among studies. This review describes how the cutoff values have been derived, and explains the issues involved in the generalization of a cutoff value. In this study, we conducted an English-language literature search in PubMed using the keywords “cotinine” and “cutoff” or “self-reported” a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
149
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(158 citation statements)
references
References 55 publications
6
149
2
1
Order By: Relevance
“…Thus, approximately 42% of participants who self-reported abstinence failed verification. We found a bimodal distribution of cotinine values consistent with samples including both non-smokers and active smokers [11, 26, 27]. Two demographic factors (African American race and lower education), one study procedural factor (in-person sample collection) and one quitting experience factor (non-continuous cessation) were significantly associated with a decreased likelihood of verifying self-reported smoking status.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, approximately 42% of participants who self-reported abstinence failed verification. We found a bimodal distribution of cotinine values consistent with samples including both non-smokers and active smokers [11, 26, 27]. Two demographic factors (African American race and lower education), one study procedural factor (in-person sample collection) and one quitting experience factor (non-continuous cessation) were significantly associated with a decreased likelihood of verifying self-reported smoking status.…”
Section: Discussionsupporting
confidence: 67%
“…While several studies have investigated the accuracy of self-reported smoking status compared to biomarkers for tobacco use [3, 11], there is little empirical evidence regarding population and study characteristics associated with discrepancies between self-report and validated abstinence in clinical trials. Factors such as education, age, race/ethnicity, diagnosis, number of smokers in the household, even inadvertent exposure to carbon monoxide have been associated with the failure of self-report to match biochemical measures [4, 8, 12].…”
Section: Introductionmentioning
confidence: 99%
“…16 A more recent review article showed that urinary cotinine cut-off levels for cotinine-verified current smoking ranged between 31.5 and 550 ng/mL. 17 Kim and Jung obtained an optimum cut-off value of 164 ng/mL for urinary cotinine using the Korea National Health and Nutrition Examination Survey database in 2008-2010 (n=11,629) and application of this urinary cotinine cut-off value had a sensitivity of 93.2% and specificity of 95.7%. 18 Kim et al 13 used a urinary cotinine cut-off level of 50ng/mL for cotinine-verified current smoking.…”
Section: Disclosuresmentioning
confidence: 99%
“…The cotinine‐based correction may not have been correct in all cases, however, as use of smokeless tobacco and other sources of nicotine may have misclassified a minority of the participants. Furthermore, the chosen cut‐off of 85 nmol L −1 , whilst reasonable, may not have been optimal . Another weakness is that smoking habits and exposure to smoke after the baseline examination were not available.…”
Section: Discussionmentioning
confidence: 99%